2006
DOI: 10.1210/en.2006-0417
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Interleukin-10 Protects against Hepatic Steatosis but Does Not Improve Insulin Sensitivity during High-Fat Feeding in Mice

Abstract: Several studies have demonstrated an association in humans between plasma levels or production capacity of the antiinflammatory cytokine IL-10 and insulin sensitivity. The aim of our study was to investigate the protective role of endogenous IL-10 availability in the development of diet-induced insulin resistance. We compared parameters of glucose and lipid metabolism between IL-10(-/-) mice and wild-type (wt) mice fed a high-fat diet for 6 wk. This diet has previously been shown to induce steatosis and insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 34 publications
4
49
0
Order By: Relevance
“…In agreement with the well-known immunomodulatory activity of IL-10 in several tissues, several studies have reported a role for IL-10 as a protective cytokine against hepatic injury in diseases such as diet-induced insulin resistance in liver (Cintra et al, 2008), experimental hepatitis induced by LPS (Santucci et al, 1996) and concanavalin A (Louis et al, 1997), schistosomiasis (Winn et al, 1998), alcoholic hepatitis (Le Moine et al, 1995), hepatitis C virus infection (Kaplan et al, 2008) and fatty liver disease (Den Boer et al, 2006). The immunosuppressive cytokine IL-10 is crucial for tolerance induction in concanavalin A-induced liver damage in mice and is mainly expressed by CD4 + CD25 + regulatory T cells (Erhardt et al, 2007).…”
Section: The Antiinflammatory Cytokine Il-10 Is Regulated By Nf-kb1 (mentioning
confidence: 53%
“…In agreement with the well-known immunomodulatory activity of IL-10 in several tissues, several studies have reported a role for IL-10 as a protective cytokine against hepatic injury in diseases such as diet-induced insulin resistance in liver (Cintra et al, 2008), experimental hepatitis induced by LPS (Santucci et al, 1996) and concanavalin A (Louis et al, 1997), schistosomiasis (Winn et al, 1998), alcoholic hepatitis (Le Moine et al, 1995), hepatitis C virus infection (Kaplan et al, 2008) and fatty liver disease (Den Boer et al, 2006). The immunosuppressive cytokine IL-10 is crucial for tolerance induction in concanavalin A-induced liver damage in mice and is mainly expressed by CD4 + CD25 + regulatory T cells (Erhardt et al, 2007).…”
Section: The Antiinflammatory Cytokine Il-10 Is Regulated By Nf-kb1 (mentioning
confidence: 53%
“…Furthermore, infliximab treatment effectively inhibited the expression of the proinflammatory cytokines, IL-6, and IL-1b, while the antiinflammatory cytokine IL-10 was not affected by the treatment. The maintenance of higher levels of IL-10 may have a positive impact on the overall result of the treatment, as suggested by recent studies that show a protective effect of this cytokine in NASH development (den Boer et al 2006, Elinav et al 2006. Another outcome of the treatment with infliximab was the reduction of SOCS-3 expression.…”
Section: Discussionmentioning
confidence: 92%
“…Interleukin 10 (IL10) is a cytokine with pleiotropic effects on immunoregulation and inflammation. It has been shown to improve insulin resistance and reduce hepatic steatosis [60] . The insulinlike growth factor binding protein 3 (IGFBP3) is one of six high-affinity binding proteins for IGFs that reduce the levels of free IGF and antagonize their insulin-like activity.…”
Section: Discussionmentioning
confidence: 99%